Validation of the Portuguese Rome III Questionnaire for Diagnosis of Functional Dyspepsia in adults - Amaral, Odete (2016)
Introduction: The validation tools are essential in epidemiological research, especially for the consensus case definition and comparison of results. Currently, the instrument most commonly used to identify functional dyspepsia is the Rome III questionnaire, which is not validated for the Portuguese population. Objectives: To validate the Rome III questionnaire for the assessment of functional dyspepsia in Portuguese adults. Methods: The questionnaire was translated following the recommendations of Rome III. A total of 166 adults completed the questionnaire. The identification of the category of functional dyspepsia among adults was based on the presence of one or more symptoms from the total of 4 symptoms that the scale allows to assess from a total of 6 items. The internal consistency, reproducibility and contents analysis were evaluated using the program SPSS 23.0. Results: Alpha Cronbach coefficient from the total of 18 items measured was 0.89. For functional dyspepsia category (assessed by 6 items) was 0.76 and the alpha Cronbach’s based on standardized items was 0.85. Conclusions: We validated, for Portugal, the Rome III questionnaire for the diagnosis of functional gastrointestinal disorders, particularly for functional dyspepsia among adults. These results suggest that this tool will be useful for research in the Portuguese population.